Một số kết quả nghiên cứu chế tạo hệ sơn không dung môi bảo vệ kết cấu thép khu vực biển và ven biển - Bích Thuỷ, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
We are currently in environmental responsible era. There is a great tendency of producing and consuming environmentally-friendly goods in all over the world. The painting industry is not an exception and non-organic solvent paints which inflict minimal harm on environment are step by step replacing traditional solvent paints. Our research has successfully processed a environmentally friendly combined paint as a barrier to prevent corrosion of steel structures in maritime climate area. This product includes the non organic solvent epoxy primer and polyurethane surface paint. The epoxy primers may contain additional materials such as sacrificial zinc to protect against corrosion and to minimize negative impacts on environment. Our findings demonstrate that the combined paint obtained is in conformity with the 22 TCN 235-97 and has a equivalent quality of EURONAVY’s none solvent paint. Keywords: Low VOC paints, epoxy paint, polyurethane paint, maritime environment, Steel reinforced concrete.